2009
DOI: 10.1161/circresaha.108.178699
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer of Redox Factor-1 Inhibits Neointimal Formation

Abstract: Key Words: apurinic/apyrimidinic endonuclease-1/redox factor-1 Ⅲ vascular smooth muscle cells Ⅲ migration Ⅲ reactive oxygen species Ⅲ spleen tyrosine kinase P latelet-derived growth factor (PDGF) performs crucial functions in the regulation of vascular cell proliferation and migration, resulting in circulatory disorders including atherosclerosis. PDGF stimulates intracellular signal molecules with Src homology 2 (SH2) domains, including Src, phospholipase C, phosphatidylinositol 3-kinase (PI3K), and ras/raf-1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…It is well known that mitogen-activated protein kinase (MAPK)s are activated by growth factors, environmental stresses and inflammatory cytokine (Chen et al, 2001). We previously reported that the overexpression of APE1/Ref-1 using the adenoviral gene transfer system inhibits TNF-α-induced ROS production and VCAM-1 in endothelial cells (Angkeow et al, 2002;Kim et al, 2006;Lee et al, 2009). In addition, p38 MAPK activation by TNF-α was blocked by overexpression of APE1/Ref-1 resulting in inhibition of TNF-α-induced VCAM-1 in endothelial cell .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that mitogen-activated protein kinase (MAPK)s are activated by growth factors, environmental stresses and inflammatory cytokine (Chen et al, 2001). We previously reported that the overexpression of APE1/Ref-1 using the adenoviral gene transfer system inhibits TNF-α-induced ROS production and VCAM-1 in endothelial cells (Angkeow et al, 2002;Kim et al, 2006;Lee et al, 2009). In addition, p38 MAPK activation by TNF-α was blocked by overexpression of APE1/Ref-1 resulting in inhibition of TNF-α-induced VCAM-1 in endothelial cell .…”
Section: Discussionmentioning
confidence: 99%
“…Many vascular diseases are characterized by the abnormal accumulation of vascular smooth muscle cells in the intima of vessels, a process that is thought to occur, in part, as a result of the migration and proliferation of these cells from the tunica media (Ross, 1999;Lee et al, 2009). Vascular smooth muscle cell migration and proliferation is induced by various inflammatory cytokines and growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, the inhibition of NADPH oxidase by Ref-1 is another pathway by which intracellular ROS levels might be reduced. It was reported previously that Ref-1 inhibited ROS production via the inhibition of the activity of rac1 GTPase, one subunit of NADPH oxidase Lee et al, 2009). A recent study reported the upregulation of the gp91phox subunit of NADPH oxidase in the brain and renal cortex of lead-exposed animals (Vaziri et al, 2003).…”
Section: Discussionmentioning
confidence: 88%
“…The enzyme is particularly important under limited glutathione content conditions, such as obtain in lead (Pb)-exposed animals (Hsu, 1981;Hunaiti et al, 1995), and plays a significant role in the development of tolerance to oxidative stress in the adaptive responses of cells (Wassmann et al, 2004 (Grosch et al, 1998;Silber et al, 2002). Conversely, overexpression of Ref-1 repair functions stimulates an increase in resistance to certain alkylating agents and oxidative stresses (Tomicic et al, 1997;Grosch et al, 1998;Kim et al, 2006;Lee et al, 2009). Ref-1 and p53 proteins are required for selenium protection from DNA damage in the human and mouse fibroblasts (Fischer et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation